Pengaruh Luas Permukaan Spesifik terhadap Kapasitansi Spesifik Elektrode Zeolit Akibat Variasi Suhu Kalsinasi - R Rosalina; S Suprihatin; Pulung Karo Karo (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2017)
The effect of specific surface area to the specific capacitance of electrode zeolite with variation of calcintion temperatures. This study describes the potential of zeolite as a supercapacitor electrode which aims to determine the effect of surface area on the specific capacitance of the zeolite. Zeolites was synthesized from a mixture of silica based rice husk and alumina using sol gel methode and was calcined at 150, 250, 350, 450, 550, and 650oC. The XRD result showed already formed alumina and silica phases for each calcinations temperature and the temperature of 350oC has formed gmelinite phase which marks have been formed zeolite. The specific capacitance increase in the specific surface area at 90.69 - 150.01 m2/g, and occurred saturation of specific capacitance at a specific surface area of 150.01 m2/g. The highest of specific capacitance is at specific surface area of 150.01 m2/g is equal to 8.13x10-3 F/g obtained from zeolites with calcination temperature of 650oC. Based on this value, the zeolite can be used as a supercapacitor electrode material.